Recent responses to the philosophy of Wittgenstein: life and language - Pandey, Kali Charan (Ludwig Wittgenstein Philosophical Society publication series, 2020)
"This anthology contains essays which explore philosophical issues which have often been raised during recent debates and discussions in Wittgensteinian epistemology, theology, logic, ethics, religion, social science, cultural studies, psychology and language. It is based on the idea that Wittgenstein's thoughts have not only been interpreted by the academicians in philosophy, but have been used as a method in many other fields of Humanities and Social Sciences as well. Keeping in view this idea, this book gives a fresh interpretation from the perspectives of recent issues raised on life and language in the philosophy of Wittgenstein. It discusses Wittgensteinian issues through Indian perspective in particular and contemporary world in general."--